2019
DOI: 10.2139/ssrn.3385107
|View full text |Cite
|
Sign up to set email alerts
|

Are Estimates of Early Education Programs Too Pessimistic? Evidence from a Large-Scale Field Experiment that Causally Measures Neighbor Effects

Abstract: Are estimates of early education programs too pessimistic? Evidence from a large-scale field experiment that causally measures neighbor effects IFN Working Paper, No. 1293

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…List, Momeni, and Zenou () found that ignoring spillover effects may dramatically reduce estimates of the actual magnitude of targeted preschool education interventions on population impact. The possibility of spillover effects suggests that estimating the population impact of a targeted intervention requires measurement and analysis of impact on the entire population, including those who are not targeted for intervention.…”
Section: Spillover Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…List, Momeni, and Zenou () found that ignoring spillover effects may dramatically reduce estimates of the actual magnitude of targeted preschool education interventions on population impact. The possibility of spillover effects suggests that estimating the population impact of a targeted intervention requires measurement and analysis of impact on the entire population, including those who are not targeted for intervention.…”
Section: Spillover Effectsmentioning
confidence: 99%
“…In such a pernicious case, a 'rigorous' individual-level trial might find that random assignment to arrest leads to initial positive impact on lowering the drug dealer's sales, whereas a population-level analysis would show adverse effects on population drug use. List, Momeni, and Zenou (2019) found that ignoring spillover effects may dramatically reduce estimates of the actual magnitude of targeted preschool education interventions on population impact. The possibility of spillover effects suggests that estimating the population impact of a targeted intervention requires measurement and analysis of impact on the entire population, including those who are not targeted for intervention.…”
Section: Spillover Effectsmentioning
confidence: 99%
“…Of course, the effect could run in the opposite direction. For example, List et al (2019) provide such an example in their measurement of the effects of a pre-K intervention in Chicago: control group children gain more than 0.5 standard deviations in cognitive test scores based on proximity to treated neighbors. This implies at scale the program may be much more effective than the original research suggests.…”
Section: But Did It?mentioning
confidence: 99%
“…Therefore, programs with greater community coalition functions, communication to stakeholders, and sustainability are more likely to still be in place over two or more years beyond their original funding (Cooper, Bumbarger, and Moore 2015). 87 Dramatic evidence of such spillovers comes from List, Momeni, and Zenou (2019a), who examine a randomized field experiment among 3-5 year olds in Chicago described in List (2015, 2017). They find that each additional treated child residing within a three kilometer radius of a control child's home increases that child's cognitive score by 0.0033 to 0.0042 standard deviations.…”
Section: Representativeness Of the Situationmentioning
confidence: 99%
“…Dramatic evidence of such spillovers comes from List, Momeni, and Zenou (), who examine a randomized field experiment among 3–5 year olds in Chicago described in Fryer, Levitt, and List (, ). They find that each additional treated child residing within a three kilometer radius of a control child's home increases that child's cognitive score by 0.0033 to 0.0042 standard deviations.…”
mentioning
confidence: 99%